Brief Report: External Beam Radiation Therapy for the Treatment of Human Pluripotent Stem Cell‐Derived Teratomas. (10th July 2017) - Lee, Andrew S.; Tang, Chad; Hong, Wan Xing; Park, Sujin; Bazalova‐Carter, Magdalena; Nelson, Geoff; Sanchez‐Freire, Veronica; Bakerman, Isaac; Zhang, Wendy; Neofytou, Evgenios; Connolly, Andrew J.; Chan, Charles K.; et al.
Abstract: Human pluripotent stem cells, including human embryonic stem cells (hESCs) and human induced PSCs (hiPSCs), have great potential as an unlimited donor source for cell‐based therapeutics. The risk of teratoma formation from residual undifferentiated cells, however, remains a critical barrier to the clinical application of these cells. Herein, we describe external beam radiation therapy (EBRT) as an attractive option for the treatment of this iatrogenic growth. We present evidence that EBRT is effective in arresting growth of hESC‐derived teratomas in vivo at day 28 post‐implantation by using a microCT irradiator capable of targeted treatment in small animals. Within several days of irradiation, teratomas derived from injection of undifferentiated hESCs and hiPSCs demonstrated complete growth arrest lasting several months. In addition, EBRT reduced reseeding potential of teratoma cells during serial transplantation experiments, requiring irradiated teratomas to be seeded at 1 × 10 3 higher doses to form new teratomas. We demonstrate that irradiation induces teratoma cell apoptosis, senescence, and growth arrest, similar to established radiobiology mechanisms. Taken together, these results provide proof of concept for the use of EBRT in the treatment of existing teratomas and highlight a strategy to increase the safety of stem cell‐based therapies. Stem Cells 2017;35:1994–2000 Abstract : Irradiation arrested hESC‐derived teratoma growth in vivo. (A): Representative BLI of teratoma growth and irradiation for immunodeficient mice seeded with 1 × 10 6 H9 hESCs constitutively expressing FLuc‐GFP on both dorsal flanks. At 28 days post‐transplantation (day 0 pre‐irradiation), the larger of the two teratomas (right side) in this example was irradiated with 6 Gy daily for 3 days (days 28‐30 post injection) for a cumulative dosage of 18 Gy while the non‐irradiated contralateral teratoma served as an un‐irradiated control. A subsequent decrease in luciferase signal was observed on the irradiated side, whereas the non‐irradiated teratomas demonstrated a progressively increasing luciferase signal. (B): Quantification of teratoma growth over time using BLI of luciferase signal from H9 hESC derivatives demonstrated growth arrest of irradiated tumors vs. control. (C): Changes in in vivo caliper measurements of teratomas over time. Non‐irradiated teratomas increased in size over time, whereas irradiated teratomas decreased in size. (D): Explanted gross teratoma specimens from day 130 post seeding. Note the significant reduction in mass in the irradiated teratoma on the right compared to the non‐irradiated teratoma on the left. * p < .05